Accumulation of soil carbon under elevated CO 2 unaffected by warming and drought - Dietzen, Christiana A.; Larsen, Klaus Steenberg; Ambus, Per L.; Michelsen, Anders; Arndal, Marie Frost; Beier, Claus; Reinsch, Sabine; Schmidt, Inger Kappel (Global change biology, 2019)
Elevated atmospheric CO 2 concentration and climate change may substantially alter soil carbon (C) dynamics, which in turn may impact future climate through feedback cycles. However, only very few field experiments worldwide have combined elevated CO 2 (eCO 2 ) with both warming and changes in precipitation in order to study the potential combined effects of changes in these fundamental drivers of C cycling in ecosystems. We exposed a temperate heath/grassland to eCO 2 , warming, and drought, in all combinations for 8 years. At the end of the study, soil C stocks were on average 0.927 kg C/m 2 higher across all treatment combinations with eCO 2 compared to ambient CO 2 treatments (equal to an increase of 0.120 ± 0.043 kg C m −2 year −1 ), and showed no sign of slowed accumulation over time. However, if observed pretreatment differences in soil C are taken into account, the annual rate of increase caused by eCO 2 may be as high as 0.177 ± 0.070 kg C m −2 year −1 . Furthermore, the response to eCO 2 was not affected by simultaneous exposure to warming and drought. The robust increase in soil C under eCO 2 observed here, even when combined with other climate change factors, suggests that there is continued and strong potential for enhanced soil carbon sequestration in some ecosystems to mitigate increasing atmospheric CO 2 concentrations under future climate conditions. The feedback between land C and climate remains one of the largest sources of uncertainty in future climate projections, yet experimental data under simulated future climate, and especially including combined changes, are still scarce. Globally coordinated and distributed experiments with long‐term measurements of changes in soil C in response to the three major climate change‐related global changes, eCO 2 , warming, and changes in precipitation patterns, are, therefore, urgently needed.